Intercultural Communication Life of Transnational Indonesian PhD Muslim Female Students in the US and Australia - Win Listyaningrum Arifin (Universitas Negeri Jakarta, 2021)
This study aimed at investigating the intercultural communication life of Indonesian PhD Muslim female students in the USA and Australia as transnationals. They face not only the language hardship but also the newest environments challenge both in academic and social setting. Stereotype, stigmatization, discrimination, and other forms of oppressions appear in relation to their visual identity. Applying Stella Ting-Toomey’ Identity Negotiation Theory, the study is to answer questions: (1) How far is the influence of the intercultural communication of these students living in a country? and (2) To what extent does intercultural communication competence influence the success of these students? This study is a qualitative descriptive based on the video/audio or diary tape of the respondents in the USA and Australia. To sum up, the video/audio or diary tape revealed that the success of intercultural communication on the these Indonesian Phd Muslim women students is influenced by knowledge, motivation, and skill obtained from the challenges in daily experiences both in academic and social life. Later, those three elements are very essential components in the ‘mindful/effectiveness intercultural communication’. Those elements become competence for Indonesian PhD Muslim women students to form adaptive strategies to overcome their internal and external situation. The process of intercultural communication might be challenging. However, the competence reveal during their first year living in a new country will be solution in facing problems or minimizing difficult situations in future years ahead.